The Critical success factors for organizational performance of SMEs in Malaysia: a partial least squares approach - Lo, May-Chiun; Yin, Chai Wang; Constance Rinen, Justin Wah; Ramayah, T. (FECAP, 2016)
Purpose – This paper seeks to examine the relationship between the determinants of organizational performance such as top management support, customer focus, employees’ orientation, technology orientation, and entrepreneurial orientation in Malaysia. Design/methodology/approach – A quantitative research design was applied for this study. Data was collected through survey questionnaires applied to business owners and senior managers working in SMEs located in three Malaysian states, using purposive sampling technique. SmartPLS 2.0 (M3) was applied to test the hypotheses. Findings – The findings suggest that both technology and entrepreneurial orientations are significant success factors for SMEs in terms of financial and non-financial performance. In addition, top management support is found to be significantly and positively related to financial performance. Originality/value – The empirical analysis indicates that technology orientation and entrepreneurial orientation add more value to organizational performance. Therefore, it is vital for SMEs to focus on these two critical success factors in order to improve their performance.